A INFLUÊNCIA DA ESCOLHA DE UM SISTEMA DE CUSTEIO NO PREÇO FINAL DA MERCADORIA EM UMA INDÚSTRIA DE PEQUENO PORTE DO SETOR PLÁSTICO NO ESTADO DO RIO DE JANEIRO - Santos, Isaias Freire dos (2008)
In an increasingly competitive market the sales prices of the products pose as a major deciding factor in consumers buying patterns. Industries in general, mainly those considered commodities industries, face a kind of rivalry primarily based on prices. Thus, by comparing the results produced by four different methods of defraying (cost of absorption, direct cost, target costing, and ABC system) applied in a small third-generation industry of the plastic sector located in the state of Rio de Janeiro, Brazil, this work aims to show which method proves more effective when it comes to deciding on prices and cost formation of manufactured products. After a study of the above-mentioned methods in the final section of this paper, we are led to the conclusion that choosing a system rather than another does affect the final price of a product and can be an asset in the light of the industry strategic position.